Technology Integration in English Language Teaching : Analysis of Teachers' Perceptions and Practices in the Digital Era - Andi Suwarni; Nurasia Natsir (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research analyzes teachers' perceptions and practices regarding technology integration in English language teaching within the Indonesian educational context. Using a mixed methods approach, this study involved 120 English teachers from various educational levels (primary, junior high, senior high, and higher education) through an online survey, with 15 teachers selected for in-depth interviews and classroom observations. The findings reveal a gap between teachers' positive perceptions of technology (M=4.21 on a 5-point scale) and actual implementation in teaching practices (M=3.15). Statistical analysis identified four main factors influencing technology integration: teachers' digital competence (β=0.43, p<0.01), institutional support (β=0.38, p<0.01), teachers' pedagogical beliefs (β=0.35, p<0.01), and infrastructure accessibility (β=0.32, p<0.01). Qualitative data revealed that while teachers acknowledge the potential of technology to increase student motivation and create authentic language learning environments, they face challenges in aligning technology use with learning objectives, classroom management, and learning assessment. This research provides recommendations for teacher professional development and educational policies that support effective technology integration in English language teaching.